A construção de estratégias: um estudo de caso no setor de telefonia móvel - Ernani Viana Saraiva (2004)
At business Administration science, strategy is the discipline which development is non linear and most fragmented. The problems presented to this might be explained trough the discussions inside the academy about it. With the main purpose of illustrate this debate, this research presents a historical revision about strategy, its discussions and researches in the world scenario and detailed perceptions of strategy investigation level in Brazil. In order to contribute to this discussion on the normative perspective, it was explored the strategic movement of an organization on the fixed communication by telephone industry which decides to enter the cellular phone industry. By using as atheoretical support the concept of strategy as a constructed reality in a iterative process, it was choose a qualitative research in order to aim the main investigation purpose. The data collection was made in two major steps, beginning with the analysis of documents produced by the organization and also the information collected at the media (newspaper, internet articles, and internal bulletin). The second step was the fieldresearch where eleven persons of the organization main board were interviewed. As a methodological strategy to analyze all the data it was decided to use the content analysis method to approach the collected data and identify the organization strategy main aspects, its dilemmas faced during the researched process and those which was abandoned, the taken decisions to resolve those dilemmas and the following strategies as the efforts to mobilize support of the demands, and finally the outcomes of those processes and their implementation as patterns of thinking. The research result shows that the strategy perspective of an organization as long as it evolves increase its complexity. The objective of retaking the strategy discussion in a broader perspective than just strategic planning revels the main contribution of the investigation in order to understand the way strategic decisions occurs in the organizations.